Optimized design of SynRM drive systems for high-efficiency solar water pumps - Boztas, Gullu; Aydogmus, Omur; Yilmaz, Musa (Elsevier Ltd, 2024)
This study presents the design and implementation of a Synchronous Reluctance Motor (SynRM) with an integrated drive circuit for a 4-inch submersible pump motor, tailored for small-scale solar photovoltaic water pumping systems. The SynRM operates efficiently at low voltage levels, eliminating the need for a boost converter and allowing direct connection to low-voltage power sources. With a power output of 0.55 kW and an ultra-premium efficiency rating of 86.5%, the motor integrates the drive circuit within its casing for a compact design. It operates across a voltage range of 15 V to 95 V, using efficient buck converters for required output voltages. This paper discusses the design, optimization, and prototyping of the motor and drive circuit, highlighting innovative solutions for advancing small-scale solar-powered water pumping systems. Electric motors, especially pump motors, are major consumers of electrical energy. Enhancing their efficiency can significantly impact total energy consumption. This study's SynRM and integrated drive system, optimized for high efficiency, durability, and cost-effectiveness, can be directly powered by PV panels, offering a compact and efficient alternative to traditional systems. © 2024 The Authors
Keywords: High efficiency; Irrigation; Solar energy; Solar water pump; Synchronous reluctance motor